(untitled) (Seminário Internacional de Informação, Tecnologia e Inovação, 2023)
The article proposes to analyze the incidence of co-authorship in scientific articles published in the magazine Informatio, a Uruguayan journal of Information Science. The research aims to understand how researchers are collaborating in their publications, identifying the predominance of patterns in the formulation of authorship and co-authorship. Methodologically, the research consisted of a comprehensive analysis of all articles published in the journal during the period from 1995 to 2023, aiming to quantify the numerical distribution of incidences. Data analysis revealed perceptions about collaboration preferences and their frequency in scientific communication with Informatio magazine as the object of study. In addition, the present investigation contextualized these trends within the journal, establishing connections with previous approaches and enriching the understanding of collaborative dynamics in the field of Information Science through systematic occurrences in the journal Informatio.